2005
DOI: 10.3748/wjg.v11.i22.3339
|View full text |Cite
|
Sign up to set email alerts
|

CIK cells from patients with HCC possess strong cytotoxicity to multidrug-resistant cell line Bel-7402/R

Abstract: AIM:To investigate the cytotoxicity of the cytokine-induced killer (CIK) cells from the post-operation patients with primary hepatocellular carcinoma (HCC) to multidrugresistant (MDR) cell of HCC both in vitro and in vivo. METHODS:A drug-resistant cell line was established by culturing human HCC cell line Bel-7402 in complete RPMI 1640 medium with increasing concentrations of adriamycin from 10 to 2 000 nmol/L. CIK cells were obtained by inducing the peripheral blood mononuclear cells with rhIFN-, monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 19 publications
(12 reference statements)
1
26
0
Order By: Relevance
“…Meanwhile, immune effector cells not only produce large amounts of inflammatory cytokines to alleviate immune damage caused by anticancer drugs and enhance the immunosurveillance capabilities of patients with cancer, 37 but additionally eliminate potential or residual tumor cells after chemotherapy, including even drug-resistant tumor cells and putative cancer stem cells. [38][39][40] Secondly, alternate application of CIK and NK cells exhibits a synergistic antitumor immunity via different mechanisms compared to the CIT with only CIK cells, which was also found by Maniar et al and Cui et al 34,35 On the other hand, it was reported that the circulating hematopoietic stem and progenitor cells from various patients with solid cancers exhibited a generalized myeloid bias with a skew toward granulocytic differentiation, 41 which increased the neutrophil-to-lymphocyte ratio (NLR), a poor prognostic indicator. 42 Adjuvant CIT could reverse the NLR, resulting in immune equilibrium to reduce tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, immune effector cells not only produce large amounts of inflammatory cytokines to alleviate immune damage caused by anticancer drugs and enhance the immunosurveillance capabilities of patients with cancer, 37 but additionally eliminate potential or residual tumor cells after chemotherapy, including even drug-resistant tumor cells and putative cancer stem cells. [38][39][40] Secondly, alternate application of CIK and NK cells exhibits a synergistic antitumor immunity via different mechanisms compared to the CIT with only CIK cells, which was also found by Maniar et al and Cui et al 34,35 On the other hand, it was reported that the circulating hematopoietic stem and progenitor cells from various patients with solid cancers exhibited a generalized myeloid bias with a skew toward granulocytic differentiation, 41 which increased the neutrophil-to-lymphocyte ratio (NLR), a poor prognostic indicator. 42 Adjuvant CIT could reverse the NLR, resulting in immune equilibrium to reduce tumor recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Two phase I clinical trials (one in patients with hepatocellular carcinoma and the other in patients with Hodgkin's disease or non-Hodgkin's lymphoma) showed significant improvement in survival of patients after reinfusion of autologous CIK cells. 25,26 Another phase I clinical trial investigated repeated administration of donor-derived CIK cells in an allogeneic transplantation setting: 27 symptoms of an acute graft-versus-host disease (grade I and II) were observed in 4/11 (36%) cases and complete responses in 3/11 (27%) cases.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, Schmidt-Wolf et al (11) first reported that CIK cells possessed potential antitumor cell activity in the immunodeficient SCID mouse/human lymphoma model. Following this finding, additional studies indicated that CIK cells may be a better choice for patients with solid tumors and demonstrated that CIKs possess strong antitumor activity in vitro (24)(25)(26). A number of previous studies have also demonstrated that CIKs may reverse drug resistance in solid tumor cells (24)(25)(26).…”
Section: Discussionmentioning
confidence: 90%
“…Following this finding, additional studies indicated that CIK cells may be a better choice for patients with solid tumors and demonstrated that CIKs possess strong antitumor activity in vitro (24)(25)(26). A number of previous studies have also demonstrated that CIKs may reverse drug resistance in solid tumor cells (24)(25)(26). Therefore CIK cell therapy has been proposed as an alternative therapeutic strategy to adopt for patients with solid tumors.…”
Section: Discussionmentioning
confidence: 99%